Learning Program Development "FindBoiliQ" (Physics Industry Boiler Base Inquiry) to Increase Learning Achievement by Reduce Impact of Physics Abstraction on High School Students - Acep Musliman (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
The "FindBoiliQ" learning program is a high school physics learning program utilizing the boiler industry (steam engine) as an inquiry-based learning object as a learning method. The research methodology in this study is a research development (Research and Development, abbreviated R & D) in the field of education. This study focuses on the development of learning programs "FindBoiliQ" is short for Physics, Industrial-Boiler and InQuiry, also is a combination of the words "Find, Boil, and iQ" The meaning contained in the 3 words of physics as high school subjects, boiler industry is the object of learning, and Inquiry is a method of learning, all three have different roles and functions to form a physics learning program that can improve student achievement. "FindBoiliQ" has characteristics based on the above word equivalents, ie; electing the concepts of physics that are considered complex given the stimulus in the form of activity visits to the object of learning to observe the implementation of physics concepts in the real world so that students have a response in the form of an increase in their curiosity on the concept that is considered complex. The strong curiosity of students is further enhanced by the interactive Multimedia (MMI) of learning that is able to imagine the concept of the abstract to something more real. The results of the "FindBoliQ" implementation in experimental class students are able to improve concept comprehension better than the students' understanding of the concept of control class with regular learning on the same concept.